Influence of Apical Clearance on Mini-Scleral Lens Settling, Clinical Performance, and Corneal Thickness Changes - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2017)
Purpose: The purpose of this work was to define the timing and magnitude of scleral contact lens settling, the factors influencing settling, and to examine whether the amount of apical clearance has an impact on clinical performance or is associated with hypoxia-induced corneal changes. Methods: Eleven patients (22 eyes) with keratoconus were fitted with a mini-scleral lens (Esclera, Brazil). Three different lenses with successively greater sagittal depths were applied to achieve 3 levels of initial apical clearance: 100 to 200 mu m (low), 200 to 300 mu m (medium), and greater than 300 mu m (high). Corneal apical clearance was measured at 15 min, 1, 2, 4, 6, and 8 hr with optical coherence tomography (OCT). Central corneal thickness was measured with OCT and Pentacam, in the morning and immediately after removal of the contact lens. Results: Mean settling was 26.8 +/- 18.8 mu m (42.7%) at 1 hr, 39.5 +/- 26.5 mu m (62.9%) at 2 hr, 50.7 +/- 31.6 mu m (80.8%) at 4 hr, 57.4 +/- 34.6 mu m (91.4%) at 6 hr, and 62.8 +/- 38.4 mu m (100%) at 8 hr. Settling rate was significantly lower in low apical clearance group (P = 0.01). The smaller diameter lenses settled more (P = 0.03). There was a slight statistically significant increase of 1.3% in central corneal thickness measured with OCT (P = 0.03). Central corneal thickness measured with Pentacam at three locations increased slightly (P = 0.001). Settling showed significant intrasubject and intersubject variations. The amount of corneal swelling and comfort scores did not differ significantly according to apical clearance. Conclusions: The average amount of settling was 62.8 mu m after 8 hr, 80% of which occurred during the first 4 hr. Slight corneal swelling (1.3%) occurred after 8 hr of wear.
Keywords: Scleral lenses; Settling; Apical clearance; Corneal edema; Hypoxia; VERSUS-HOST-DISEASE; SEVERE DRY EYE; CONTACT-LENSES; IRREGULAR CORNEAS; OXYGEN DIFFUSION; MANAGEMENT; PROSE; WEAR